Active interaction control of civil structures. Part 1 SDOF systems. - Zhang, Yunfeng
This paper presents a family of semi-active control algorithms termed as active interaction control (AIC) used for seismic response control of civil structures. AIC control algorithms include active interface damping (AID), optimal connection strategy (OCS) and tuned interaction damping (TID). A typical SDOF AIC system consists of a primary structure, an auxiliary structure and an interaction element. The auxiliary structure typically has stiffness comparable to that of the primary structure while its natural frequency is much higher than that of the primary structure. Interactions between the primary and the auxiliary structures are defined by specific AIC control logic such that vibrational energy is extracted from the primary structure into the auxiliary structure during a locking phase and dissipated in the auxiliary structure in the subsequent unlocking phase. The stability of AIC control algorithms is shown using Lyapunov direct method. The efficacy of AIC control algorithms is demonstrated by the results of numerical simulations of SDOF systems subjected to seismic ground motions. Practical issues such as sampling period and time delay are also investigated in this study.
Keywords: Structural control; Semi-active control; Seismic response; Time delay